Experimental and numerical studies on the premixed syngas swirl flames in a model combustor - Samiran, Nor Afzanizam; Chong, Cheng Tung; Ng, Jo Han; Tran, Manh Vu; Ong, Hwai Chyuan; Valera-Medina, Agustin; Chong, William Woei Fong; Mohd Jaafar, Mohammad Nazri (Elsevier, 2019)
Experimental and numerical investigations were performed to study the combustion characteristics of synthesis gas (syngas) under premixed swirling flame mode. Four different type of syngases, ranging from low to high H2 content were tested and simulated. The global flame structures and post emission results were obtained from experimental work, providing the basis of validation for simulations using flamelet generated manifold (FGM) modelling approach via a commercial computational fluid dynamic software. The FGM method was shown to provide reasonable agreement with experimental result, in particular the post-exhaust emissions and global flame shapes. Subsequently, the FGM method was adopted to model the flame structure and predict the radical species in the reaction zones. Simulation result shows that H2-enriched syngas has lower peak flame temperature with lesser NO species formed in the reaction zone. © 2019 Hydrogen Energy Publications LLC